Procesy integracyjne w Polsce w latach 1994–2016 w ocenie mniejszości arabskiej - Abou Saleh, Ziad (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2017)
The article concerns the processes of integration, acculturation, education and the existence of Arabs in Poland, based on the results of empirical research conducted among groups of young Arabs studying in Poland in 1994 (610 people). From this group, after 21 years, it was possible to find 132 people and carry out further research with their participation; study was continued also in 2016 on a similar group of 38 people. The aim of this work is the comparative analysis of changes in attitudes of Arabs living in Poland, with regards to Polish society, and the assessment of the effectiveness of integration and cultural assimilation, after 20 years of residence in the new environment.
Keywords: Arab; Pole; image; integration; assimilation; migration crisis